A serious shoot and leaf disease caused by Colletotrichum theobromicola discovered on eucalypts in South Africa. Issue 1 (2nd January 2022) - Solís, Myriam; Wingfield, Michael J; Greyling, Izette; Pham, Nam Q
Abstract : Eucalypt plantations in South Africa make up an important part of the local forestry industry. Recently, one-year-old nursery plants of a Eucalyptus grandis × Eucalyptus urophylla variety displayed symptoms of leaf and shoot anthracnose disease. Samples were collected from these plants and isolations were made from the disease symptoms. Isolates were identified based on their morphological characteristics and DNA sequence data for eight gene regions. Phylogenetic analyses led to the isolates being identified as Colletotrichum theobromicola and the reduction of Colletotrichum pseudotheobromicola to synonymy with the former species. Pathogenicity trials with isolates of C. theobromicola were conducted on clones of E. grandis and hybrids of E. grandis × E. urophylla and E. grandis × Eucalyptus camaldulensis. Resulting symptoms were similar to those found on naturally infected plants and the fungus was re-isolated from the infections. Colletotrichum theobromicola is known to cause anthracnose on various plants including eucalypts in Brazil, but this is the first record of the pathogen in South Africa.